The effects of computer-aided learning on retention. - Rodil, Donna Bella B.
This study investigated the relationship hypothesized to exist between the type of learning methods and subject areas and student's retention measured through examination performance. the participants were randomly selected Hum II and Math 14 students fromt he University of the Philippines in the Visayas, College of Arts and Sciences, enrolled during th second semester of AY 1998-99. The instrument used for the dual - mode instruction (computer - aided learning) was an interactive multimedia program adapted from Interactive Multimedia Britannica Encyclopedia for Hum II and from Prol trigonometry for Math 14 subject. For the participants under the single - mode, printed counterpart of the multimedia program was used. The statistical tool employed in determining the relationship between the variables studied was Two - Way Analysis of Variance for the 2 (subject area) X 2 (learning method) factorial design. This was used to establish if there is any significant difference existed in the retention of students who used different learning methods in different subject areas. The findings of this study showed that there was a significant interaction between subject areas F(1,56) = 5.53, p <0.05 and also between learning methods F(1,56) = 5.07, p < 0.05. Nevertheless, there was no significant interaction effect (F1,56) = 0.08, p < 0.05 found among all variables.